A comprehensive review on magnetically controllable reactor: Modelling, applications and future prospects. (November 2021) - Mehmood, Kashif; Cheema, Khalid Mehmood; Tahir, Muhammad Faizan; Saleem, Adeel; Milyani, Ahmad H.
Abstract: Renewable energy sources are commonly available on earth; thus, both research and practical applications have drawn significant interest. In the large-scale renewable energy system, power quality in the grid, particularly harmonics and flickers, has a massive influence on the grid system. Recent years have seen enormous use of magnetically controllable reactors (MCRs) to solve these power quality problems. MCR can provide reactive power and voltage regulation in ultra and high voltage power grid, suppress power frequency and overvoltage operation, eradicate generator self-excitation, dynamically adjust power charging in a transmission line, suppress secondary arc current, damping system resonance, and so on, which can meet the different needs of the modern system. Considering MCR's development status, this paper provides a detailed theoretical analysis of MCR and its configurations. Moreover, voltage and reactive power control mechanisms and other associated economic and technical factors and relevant application selection are explained in detail. It aims to give the researchers and application engineers dealing with power quality issues a broad perspective on MCR technology's status. Finally, the MCR issues and future directions for research are discussed. A list of more than 280 research publications on the subject is also linked for a quick reference.